Effectiveness of tax incentives in optimizing corporate income tax revenue: Case study public listed company tax office - Innekeputri, Nindia; Aribowo, Irwan (WIM Solusi Prima, 2024)
Tax revenue is a key component of the Indonesian State Budget (APBN) and plays a strategic role in national development. This study aims to analyze the impact of the implementation of the income tax rate reduction policy and tax incentives based on Law Number 7 of 2021 on Harmonization of Tax Regulations (UU HPP) on corporate income tax revenue at Public Listed Company Tax Office. The research methodology used is qualitative descriptive, with primary data obtained through interviews with tax officials and tax consultants, and secondary data from tax revenue documentation and related literature. The findings show that the reduction in corporate income tax rates and the provision of tax incentives for publicly listed companies significantly impact the optimization of tax revenue at the Public Listed Company Tax Office. The largest contribution to corporate income tax revenue comes from companies listed on the Indonesia Stock Exchange (IDX), with a dominant contribution from companies conducting Initial Public Offerings (IPOs). The study also identifies several factors affecting the optimization of corporate income tax revenue, including tax awareness and corporate tax morale. These findings provide important insights into how tax policies can be optimized to improve taxpayer compliance and tax revenue, as well as their contribution to national economic growth.